CHANGES IN POETIC FORM IN NEW UZBEK POETRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the changes in the poetic form in the new Uzbek poetry are based on the example of Muqimiy, Avloniy work.The measurements of poetry in the new Uzbek literature and the analysis of the use of poetry forms to live language, the closest to the tones of people's creativity are used.